Entrepreneurial Passion and Venture Capitalists’ Willingness to Invest: The Role of Relational Capital - Yang, Hongtao; Shi, Hangyu; Wu, Yenchun Jim; Zhang, Lei; Xie, Shuting (Frontiers in Psychology, 2021)
Venture capital investment has serious conflicts of interest and information asymmetry. Venture capitalists often make investment decisions on the basis of the passion of entrepreneurs, including enthusiasm and preparedness, in the process of interacting with them. Most of the previous research on relational capital have focused on the cooperative relationship between suppliers and buyers. However, the role of relational capital in the process of partnership between venture capitalists and entrepreneurs has not been revealed. On the basis of signaling theory, we explore the relationship between entrepreneurial passion and venture capitalists’ willingness to invest. We also examine the mediating and moderating roles of relational capital. This study takes 79 projects between venture capitalists and entrepreneurs as samples for empirical analysis to verify our hypothesis. Results show that entrepreneurs’ enthusiasm and preparedness have a significant positive impact on venture capitalists’ willingness to invest. Relational capital plays a mediating role between entrepreneurial passion and venture capitalists’ willingness to invest. Relational capital positively moderates the relationship between preparedness and venture capitalists’ willingness to invest but has no moderating effect between enthusiasm and venture capitalists’ willingness to invest. Results deepen the understanding of the relationship between entrepreneurs’ passion and venture capitalists’ willingness to invest, which has guiding significance for venture capital practice in China.